Kemampuan Berfikir Spasial dalam Pembelajaran Abad 21 - Bayu Wijayanto; Widia Sutriani; Farisha Luthfi (Geography Education Study Program, Universitas Samudra, 2020)
At this time the learning system is based on digital technology so that students can develop abilities and be competitive. Besides, the Problem Based Learning (PBL) model is also a way to train students to be able to think creatively in solving problems encountered. The purpose of this study is to determine the form of learning in the 21st century, spatial intelligence in geography learning and its urgency, and Problem Based Learning in improving spatial thinking skills. The method used is the study of literature and experiments. Literature studies are used in analyzing problems related to learning in the 21st century and spatial intelligence. While the experimental method is used to see the ability of spatial thinking with Problem Based Learning models. The results of this study are the forms of learning in the 21st century today based on digital technology because human resources began to be replaced by artificial intelligence following the times. Spatial intelligence in geography learning becomes a basic ability that must be possessed by students because it is related to the ability to assess a phenomenon spatially. Problem Based Learning Model that applies students' spatial intelligence with a tcount of 10.43 > ttable 2.03